Improving adherence to cardiovascular guidelines: realistic transition from paper to patient. (2nd January 2020) - Mahtta, Dhruv; Rodriguez, Fatima; Jneid, Hani; Levine, Glenn N.; Virani, Salim S.
ABSTRACT: Introduction : The emphasis on clinical trials to inform evidence-based medicine remains paramount within the cardiovascular community. Although such high-quality evidence is often translated into national and international guidelines, there exists a large gap between guideline development and guideline implementation into daily clinical practice. Areas covered : This article outlines barriers that impede guideline adherence and possible strategies to overcome such barriers. Barriers intrinsic and extrinsic to clinicians are discussed. The structured process of guideline implementation including guideline adoption, diffusion, and dissemination is discussed. Lastly, the authors review in detail the current and potential future elements of guideline diffusion and dissemination. Expert opinion : Improving guideline adherence remains challenging as it requires understanding of and navigation through various barriers. However, further research specific to cardiovascular medicine guidelines is necessary to better understand the objective effectiveness of various strategies employed by guideline writers and medical societies to improve adherence. The cost-effectiveness of nationwide dissemination strategies in improving guideline adherence and patient outcomes is also necessary but is largely unknown.